2014
DOI: 10.1111/liv.12626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of toll‐like receptor 7 and 9 targeted therapy to prevent the development of hepatocellular carcinoma

Abstract: Background & Aims: Chronic liver disease is a predisposing factor for development of hepatocellular carcinoma (HCC). Toll-like receptors play a crucial role in immunity against microbial pathogens and recent evidence suggests that they may also be important in pathogenesis of chronic liver disease. The purpose of this study was to determine whether TLR7 and TLR9 are potential targets for prevention and progression of HCC. Methods: Tissue microarrays containing liver samples from patients with cirrhosis, viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 53 publications
(58 reference statements)
3
51
0
Order By: Relevance
“…Stimulation of TLR7 in a pancreatic cancer model expressing TLR7 induces tumor growth acceleration and reduction in antitumor molecules expression [299,300]. Similarly, TLR7 stimulation in hepatocellular carcinoma model expressing TLR7 boost malignant cells proliferation [301].…”
Section: Implications In Cancersmentioning
confidence: 98%
See 1 more Smart Citation
“…Stimulation of TLR7 in a pancreatic cancer model expressing TLR7 induces tumor growth acceleration and reduction in antitumor molecules expression [299,300]. Similarly, TLR7 stimulation in hepatocellular carcinoma model expressing TLR7 boost malignant cells proliferation [301].…”
Section: Implications In Cancersmentioning
confidence: 98%
“…All these mechanisms of action highlight the anti-inflammatory and immuno-suppressive activity of this antimalarial drugs by acting on endosomal TLR signaling (TLRs 7/8/9). Moreover, CQ was under investigation for diseases associated with uncontrolled acute or chronic inflammation (severe sepsis [313]), to prevent and treat viral infections (HIV, influenza, and dengue) [314,315], cardiovascular diseases [316] or cancer by notably modulating autophagy [317]. Long term HCQ administration ameliorate hypertension and aortic endothelial dysfunction in a SLE mouse model [318].…”
Section: Bicycles Analoguesmentioning
confidence: 99%
“…Chloroquine (CQ), the antimalarial drug that inhibits the function of endosomal TLRs, has been shown to inhibit the endosomal TLR7 signalling effectively 17,18 . Although most studies have been reported on the role of TLR7 in inflammation and cancer, little is known in AKI with T1DM.…”
mentioning
confidence: 99%
“…These data indicate that TLR7 is downregulated in HCV-related HCC. However, Mohamed et al (2015) reported different results. Their data, produced by immunohistochemistry staining, showed that TLR7 and TLR9 were both overexpressed in the HCC tissues compared with those from cirrhosis and viral hepatitis cases.…”
Section: Expression Of Tlrs In Hepatocellular Carcinoma (Hcc)mentioning
confidence: 85%